2015
DOI: 10.1590/1806-9282.61.04.362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two analgesia protocols for the treatment of pediatric orthopedic emergencies

Abstract: Results: 13 patients were allocated to ketamine and 12 to morphine, without differences in relation to age, weight, gender, type of injury, and pain scale before the intervention. There was no failure in any of the groups, no differences in time to start the intervention and overall procedure time. The average hospital stay time was similar (ketamine = 10.8+5.1h versus morphine = 12.3+4.4hs; p=0.447). The median pain (faces pain scale) scores after the procedure was 2 in both groups. Amnesia was noted in 92.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Embora esses métodos nem sempre são aplicáveis em unidades de terapia intensiva devido à presença de tubo endotraqueal e ventilação mecânica. O uso de escalas para dor pode ser um item adicional no momento da alta do paciente (BARCELOS et al, 2015).…”
Section: Resultsunclassified
“…Embora esses métodos nem sempre são aplicáveis em unidades de terapia intensiva devido à presença de tubo endotraqueal e ventilação mecânica. O uso de escalas para dor pode ser um item adicional no momento da alta do paciente (BARCELOS et al, 2015).…”
Section: Resultsunclassified
“…At high doses drug causes hallucination, disturbed sleep, increased intracranial pressure, high blood pressure, tachycardia, and tonic-clonic seizure [7]. Several studies have shown that ketamine is effective agent in the treatment of pain [8] and morphine is the most commonly used analgesic in emergency centers [5,[9][10][11][12][13][14][15][16]. Intravenous ketamine is an available agent associated with minimal complications and side effects while the morphine is less available and associated with several side effects such as tolerance [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%